ISOLATION OF SALMONELLA SPP. FROM SLAUGHTERED SHEEP IN BASRA - Wessam M. Mohammed Saleh (Basrah Journal of Veterinary Research)
This study was carried out for detection of Salmonella isolates from 309 different apparently healthy samples (97 fecal, 71 bile, 102 intestinal content, 18 livers and 21 spleen) collected from slaughtered sheep in a slaughterhouse in Basra during the period between September to November 2010. The results revealed that the incidence rate of salmonella isolates in fecal samples was 7.2 %, in bile samples 8.5 % and in intestinal content 9.8%. While no isolations were obtained from the liver and spleen samples. The total positive sample of salmonella isolates was 23 (7.4%).